Medicinal Plants for Pain Relief in the Sasak Ethnic Tradition: A Literature Review: Review Pemanfaatan Tumbuhan Obat Sebagai Pereda Nyeri Dalam Tradisi Etnis Sasak - Bella, Aisyah; Luthfiyanti, Alya Afifah; Nurlita, Adinda Dwi; Maula, Atiqotul (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
Ethnomedicine is a study of the perceptions and constructions of local people in understanding the concept of health and the practice of traditional medicine systems that develop in an ethnic community. Sasak ethnicity is known to have quite rich local knowledge about various types of plants used in healing diseases, including for pain relief. Pain relievers are substances or materials used to reduce or eliminate pain, both acute and chronic. The purpose of this paper is to convey the various plants that are used as pain relievers for a number of diseases among the Sasak ethnic group, and to explore whether there is scientific evidence that supports the effectiveness of their use based on a review of relevant literature. Systematic Literature Review (SLR), in which various scientific articles were collected from a number of databases such as Google Scholar, PubMed, ScienceDirect, and ResearchGate. The results show that the types of plants most widely used by ethnic Sasak in medicine are ginger (Zingiber officinale), betel (Piper betle), and kencur (Kaempferia galanga) because of their secondary metabolite content which is anti-inflammatory, analgesic, and antimicrobial. The most utilized part of the plant is the leaves (55.5%) because they are easy to obtain and rich in bioactive compounds. The dominant processing methods are boiling (45%) and pounding (37%), while the most common mode of use is drinking (55%). The most commonly treated ailments include fever and heat, followed by headache, internal heat, and wounds.